Morphology prediction of Carbamazepine-Saccharin co-crystal in ethanolic solution using molecular simulation - Mohammad Zikri, Zahari; Saidatul Shima, Jamari; Nornizar, Anuar; Syarifah, Abd Rahim (AIP Publishing, 2025)
Co-crystal formation between a drug and a co-crystal former shows promising potential in improving the drug’s solubility, dissolution, and physicochemical properties, however this may not be true in all situation, with molecular simulation might give an insight to why this occurs. In this work, carbamazepine (drug) and saccharine (co-crystal former) were chosen as a model compound due to their attractive crystal chemistry and its diverse surface properties. The aim of this study is to analyses the morphology of carbamazepine-saccharin co-crystal using molecular simulation. Prediction of carbamazepine-saccharin co-crystal morphology was conducted with condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS), COMPASS II, Dreiding, Universal, Consistent Valance Force Field (CVFF) and Plymouth Consistent Force Field (PCFF) with two different charges, one is Gasteiger and the other is QEq Charge Equilibration, which produces granular/pebble like shape for Carbamazepine Form III, plate shape morphology for Carbamazepine-Saccharin and hexagonal plate shape for Saccharin, and shows good agreement with the experimental crystal shape. The results shows that the prediction using COMPASS with QEq charges for Carbamazepine, Carbamazepine-Saccharin and Saccharin to be the most stable given the predicted energy was -373.2077 kcal/mol, -303.5923 kcal/mol and -357.5599 kcal/mol respectively. In addition, seventeen morphological important facets were produced; (011), (002), (10-1), (101), (110), (11-1), (020) for Carbamazepine, (001), (010), (100), (110), (101), (111), for Carbamazepine-Saccharin and (100), (011), (002), (10-2) for Saccharin, and their multiplicity.